Electroacupuncture alleviates spatial memory deficits in METH withdrawal mice by enhancing astrocyte‐mediated glutamate clearance in the dCA1. (14th June 2021) - He, Teng; Li, Nanqin; Shi, Pengbo; Xu, Xing; Nie, Jiaxun; Lu, Xue; Yu, Peiyao; Fan, Yu; Ge, Feifei; Guan, Xiaowei
Abstract: Methamphetamine (METH) elicits endogenous glutamate (Glu) in the brain, which could partially explain METH‐induced memory deficits. Here, we investigated the therapeutic effects of electroacupuncture (EA) on spatial memory deficits in METH withdrawal mice and its potential synaptic mechanisms. We found that EA at acupoints 'Baihui' and 'Yintang' ameliorated the impaired spatial memory in METH withdrawal mice. In parallel, EA attenuated the Glu levels in vivo and suppressed the neuronal activities within dCA1 of METH withdrawal mice, as indicated by the decreasing c‐Fos levels and the amplitude of mEPSP. In the dCA1, EA decreased A1‐like astrocytes but increased astrocytic glutamatergic transporting molecules including glutamate transporter 1 and glutamine synthase. However, EA seemed to have no effects on presynaptic Glu transmission from the dCA3, as evidenced by the similiar levels of c‐Fos in the dCA3 neurons, synaptic vesicular markers of dCA3 neural terminals and values of paired‐pulse ratio in the dCA1 neurons between EA‐treated and sham EA‐treated METH withdrawal mice. These findings suggest that EA might normalize the dCA1 Glu levels at least in part through enhancing astrocyte‐mediated Glu clearance. Taken together, astrocytes might be a novel target for developing therapeutic interventions against the impaired memory behaviours in METH users, and EA represents a promising non‐invasive therapeutic strategy for the management of drug‐caused memory deficits. Abstract : EA at acupoints 'Baihui' and 'Yintang' ameliorates the spatial memory deficits and hyperglutamatergic status in METH withdrawal mice through restoring astrocyte‐mediated glutamate clearance at the tripartite synapses of the dCA1.